Factors associated with the use of important human antimicrobials in Japanese small-animal clinics - Makita, Kohei; Yoshida, Mao; Ukita, Makoto; Matsuoka, Takeshi; Sakai, Masato; Tamura, Yutaka (Frontiers in Veterinary Science, 2025)
IntroductionIn Japan, programs to monitor antimicrobial use in companion animals have not been established. To fill this gap, the Japan Veterinary Medical Association has conducted surveys of actual use. The aims of this paper are to clarify the frequency and factors associated with the use of human antimicrobials in Japanese small-animal clinics.MethodsAntimicrobial usage and awareness surveys were conducted at 260 veterinary clinics between November 2021 and February 2022 using two questionnaires. The annual use of each antimicrobial drug was categorized by frequency, and the median value of each category, with a score of 50 for the choice ≥50, was used to quantify usage frequency. Important antimicrobial drugs for human use were defined as rank I antibiotics of the Food Safety Commission. Knowledge and awareness factors associated with the use of important antimicrobial drugs for human use were analyzed using three approaches. First, the use of important drugs was examined using a generalized linear model (GLM) with binomial errors. Second, a vector generalized linear and additive model with zero-inflated binomial errors was used to evaluate the proportion of important drugs among the annual frequency of use of human antimicrobial drugs. Third, at the drug level, selecting veterinary clinics using important human drugs, univariable GLMs with Poisson errors were used to evaluate the frequency of important human drug use, with the log number of employees as the offset term.ResultsThe response rates were 71.2 and 72.3% for the antimicrobial usage and awareness surveys, respectively. All of the facilities used human antimicrobial drugs, and 57.1% (93/163) of facilities used important human antimicrobial drugs. Important human antimicrobial drugs accounted for 21.7% of the frequency of use of human antimicrobial drugs annually (7,342/33,896 times). In terms of the proportion of important human drugs and frequency of important human drug use, the use of important human antimicrobial drugs was low in cases of high awareness of prudent use of antimicrobial drugs and where tests for evidence-based judgment were introduced, but was high when price and ease of use were emphasized.DiscussionAntibiotic stewardship should be further promoted in Japanese small-animal clinics through educational and information dissemination activities.